Kesejahteraan Psikologis Mahasiswa Hafiz Alquran - Novita Sari; Zainal Abidin (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2022)
This study aims to explore the psychological well-being of hafiz Qur'an students. Psychological well-being is an individual's psychological health condition that has optimal positive psychological function. The positive psychological function refers to six dimensions, namely: self-acceptance, positive relationships with others, autonomy, environmental mastery, purpose in life and self-growth. This research used a phenomenological qualitative method with thematic analysis. Participants were five hafiz students who were selected through snowball sampling. The results of the study show that the motivation of hafiz students in memorizing the Qur'an is to give a crown of glory to their parents in the afterlife. This shows the direction and purpose of life that is oriented towards happiness in the hereafter. The representation of other psychological functions is also seen as a desire to continue to grow to become a better person, accept strengths, weaknesses and the past, manage daily activities, have self-autonomy and establish positive relationships with others. In addition, doing murojaah can provide peace.